Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10658-011-9919-7
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of postharvest diseases of fruit

Abstract: Postharvest decay in harvested fruit causes considerable economical losses. Fungicides are the primary means to control these losses. Public concern in food safety and environmental issues and the increase of pathogen resistant populations have enhanced the interest in developing alternative methods to fungicides to control postharvest fruit decay. During the last two decades a huge information and advances concerning the selection of antagonists, mode of action, different approaches to enhance biocontrol acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
140
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(155 citation statements)
references
References 112 publications
2
140
0
13
Order By: Relevance
“…5 This is due to increasing concerns regarding the environmental impacts of synthetic pesticides, as well as stricter controls on their use and the appearance of fungicide-resistant strains. 1,6 Given the importance of developing new biopesticides and investigating their spectra of action, a recent survey showed promising results with the allelopathic plant Conyza canadensis (L.) Cronquist, which belongs to the Asteraceae family and is popularly known as horseweed. 7 This plant is a potential source of bioactive compounds 8 and several studies have reported the fungitoxic effects of its essential oils, [9][10][11] although the compounds responsible for such activity were not identified.…”
Section: Introductionmentioning
confidence: 99%
“…5 This is due to increasing concerns regarding the environmental impacts of synthetic pesticides, as well as stricter controls on their use and the appearance of fungicide-resistant strains. 1,6 Given the importance of developing new biopesticides and investigating their spectra of action, a recent survey showed promising results with the allelopathic plant Conyza canadensis (L.) Cronquist, which belongs to the Asteraceae family and is popularly known as horseweed. 7 This plant is a potential source of bioactive compounds 8 and several studies have reported the fungitoxic effects of its essential oils, [9][10][11] although the compounds responsible for such activity were not identified.…”
Section: Introductionmentioning
confidence: 99%
“…In the industrialized countries, it is estimated that loss can be up to 25% of harvested fruits. The situation is far more exacerbating in the developing countries, where postharvest loss can be over 50% in some areas (Nunes, 2012). Fresh produce is decayed by pathogens during post harvesting and handling (Sharma et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of wild species and strains of antagonistic yeast species is recognized as one of the promising alternatives. Since Wilson and Wisniewski proposed the first principles and concepts of postharvest biocontrol (2, 3), numerous reviews have been published (4)(5)(6)(7)(8)(9)(10)(11). Research has focused on a wide variety of topics.…”
mentioning
confidence: 99%